Peran Implementasi Strategi Customer Relationship Marketing (Crm) Terhadap Peningkata Penjualan “Go Sport Makassar” Di Masa Lockdown Pandemi Covid 19 (Studi Kasus Pada Toko Go Sport Makassar) - Nur Fatma; Makkira Makkira; Asriani Asriani (YUME : Journal of Management, 2021)
Abstrak The role of the implementation of the Customer Relationship Marketing (CRM) strategy on increasing sales of the "Go Sport Makassar" Store during the Covid 19 Pandemic lockdown. The data used in this study using primary data is raw data taken by the researchers themselves from the main source, the data used in this study is raw data taken by the researchers themselves from the main source, collected through instruments: interviews/interviews, observations/observations. Sources of data used in this study include direct observation in the field interviews with Ouner shops.The results of this study show that the implementation of Customer Relationship Marketing (CRM) on Go Sport Makassar is going well, so it can maintain sales of sports clothing in the midst of the covid 19 pandemic, this system is very useful for Go Sport Makassar stores due to the many sports needs in the midst of a pandemic. Keywords: CRM, Sales Level